Effects of different spatial distributions of physical soil crusts on runoff and erosion on the Loess Plateau in China. Issue 13 (27th June 2017) - Lu, Pei; Xie, Xinli; Wang, Linhua; Wu, Faqi
Abstract: The response of runoff and erosion to soil crusts has been extensively investigated in recent decades. However, there have been few attempts to look at the effects of spatial configuration of different soil crusts on erosion processes. Here we investigated the effects of different spatial distributions of physical soil crusts on runoff and erosion in the semi‐arid Loess Plateau region. Soil boxes (1.5 m long × 0.2 m wide) were set to a slope of 17.6% (10°) and simulated rainfall of 120 mm h −1 (60 minutes). The runoff generation and erosion rates were determined for three crust area ratios (depositional crust for 20%, 33%, and 50% of the total slope) and five spatial distribution patterns (depositional crust on the lower, lower‐middle, middle, mid‐upper, and upper slope) of soil crusts. The reduction in sediment loss ('sediment reduction') was calculated to evaluate the effects of different spatial distributions of soil crusts on erosion. Sediment yield was influenced by the area ratio and spatial position of different soil crusts. The runoff rate reached a steady state after an initial trend of unsteadily increasing with increasing rainfall duration. Sediment yield was controlled by detachment limitation and then transport limitation under rainfall. The shifting time of erosion from a transport to detachment‐limiting regime decreased with increasing area of depositional crust. No significant differences were observed in the total runoff among treatments, while the total sediment yield varied under different spatial distributions. At the same area ratio, total sediment yield was the largest when the depositional crust was on the upper slope, and it was smallest when the crust was deposited on the lower slope. The sediment reduction of structural crust (42.5–66.5%) was greater than that of depositional crust (16.7–34.3%). These results provide a mechanistic understanding of how different spatial distributions of soil crusts affect runoff and sediment production. Copyright © 2017 John Wiley & Sons, Ltd.